2012
DOI: 10.3402/tellusa.v17i3.9067
|View full text |Cite
|
Sign up to set email alerts
|

Cloud droplet collision efficiency in electric fields

Abstract: A mathematical model describing the effects of forces acting on two spherical droplets immersed in a viscous medium is described. The model includes the interaction of the droplets with an externally applied electric field. The collision efficiencies between pairs of droplets ranging in size from 5 to 70 microns in radius are given as results of computations of the grazing trajectories of the smaller droplets relative t o the larger drops in electric fields up to 10,000 volts per centimeter.The collision effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
0
10
1
Order By: Relevance
“…Certainly E• and/or E•. are affected by charging, as has been shown by Plumlee and Semonin [1965] and Neiburger et al [1974], respectively. The tendency seems to be an enhancement of E• and E•., though our treatment Levin 1974, 1975b] adequately shows that either enhancement or depletion effects can be expected.…”
Section: Errorsmentioning
confidence: 82%
“…Certainly E• and/or E•. are affected by charging, as has been shown by Plumlee and Semonin [1965] and Neiburger et al [1974], respectively. The tendency seems to be an enhancement of E• and E•., though our treatment Levin 1974, 1975b] adequately shows that either enhancement or depletion effects can be expected.…”
Section: Errorsmentioning
confidence: 82%
“…(3.3 KV/cm). Plumlee & Semonin (1965) found that the collision efficiency of a 50 /mi radius drop with a 10 pm droplet increases by a factor of about 1.3 when the horizontal field is changed from 0 to 3 600 V/cm, while in the same range of field strength the collision efficiency increases by a factor of 34.5 for the 30 and 5 pm droplet pair.…”
Section: Collision Efficiencymentioning
confidence: 95%
“…Computations of electric field influence on droplet collision efficiency have been made by several workers, especially by Krasnogorskaja (1965), Plumlee & Semonin (1965), and Sartor (1967). Krasnogorskaja (1965) predicts that two uncharged droplets of radius 15 pm and 25 pm having a collision efficiency of about 0.8 in the absence of a field, will attain values of 1.6, 5.2 and 8.4 in a vertical electric field strength of 2, 6, 10 KV/cm respectively.…”
Section: Collision Efficiencymentioning
confidence: 99%
“…where ρ a (kg/m 3 ) and ρ p (kg/m 3 ) are the air and snow particles density, respectively; D (m) is the diameter of the cables; d p (m) is the diameter of the snow particles; and μ (pa•s) is the dynamic viscosity of the medium environment, which is air in this study. Several investigations have been done on collision efficiency of different types of atmospheric icing on objects with different geometries such as cylinder [23][24][25][26], stranded power transmission lines [27], and airfoils [28,29]. Wakahama had studied trajectories of snow particles by photographing them when they were impinging to or rebouncing from a cylindrical surface [30].…”
Section: Eoretical Sectionmentioning
confidence: 99%